Treatment of severe spacticity in multiple sclerosis by continuous intrathecal baclofen - Perić Predrag; Antić Branislav; Dinčić Evica; Obradović Dragana; Arsić Stojanka (Vojnosanitetski Pregled)
Background. Successful treatment of severe spasticity represents an imperative of symptomatic therapy of multiple sclerosis (MS) due to a significant improvement of physical, psychic and social rehabilitation of MS patients, as well as a longterm cost savings for the additional treatments of conditions arising from uncontrolled severe spasticity. Continuous intrathecal administration of baclofen (ITB), using a subcutaneously implanted programmable infusion pump, is a minimally invasive, reversible method for the treatment of severe diffuse spasticity of the spinal origin. Case report. The first two cases in our country, treated by ITB due to severe spasticity caused by MS, were reported. Despite the local complications of surgical wound healing above the implanted components of the ITB-system in one patient, the optimal reduction of spasticity the with complete elimination of spastic pain was obtained in both patients. Conclusion. Our initial experiences confirmed ITB as a safe and effective therapeutical option for the treatment of intractable spasticity in patients with MS. Major prerequisites for this were adequate patient selection and good control of the basic disease. The use of the minimal invasive implantation technique and the experience in choosing of the adequate ITB-system components, could successfully prevent the occurrence of local complications related to the impaired healing of the ITB-system implantation site.